2022
DOI: 10.1002/cam4.4664
|View full text |Cite
|
Sign up to set email alerts
|

The role of microvesicles as biomarkers in the screening of colorectal neoplasm

Abstract: Background Colorectal cancer (CRC) is the second cause of cancer death worldwide. The role of circulating microvesicles as a screening tool is a novel, yet effective approach that warrants prioritised research. Methods In a two‐gate diagnostic accuracy study, 35 patients with benign colorectal polyps (BCRP) (n = 16) and colorectal cancer (CRC) (n = 19) were compared to 17 age‐matched healthy controls. Total annexin‐V positive microvesicles and sub‐populations positive for selected biomarkers relevant to bowel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 56 publications
0
1
0
Order By: Relevance
“…In our study, we used Annexin V, whereas Zhao et al [38] used lactadherin, which has been shown to be more effective in isolating MVs [39,40]. Eddama et al, 2022, similarly demonstrated elevated levels of MVs in CRC patients, supporting our data and further pointing out the role of MVs as a potential biomarker for early disease detection [21].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In our study, we used Annexin V, whereas Zhao et al [38] used lactadherin, which has been shown to be more effective in isolating MVs [39,40]. Eddama et al, 2022, similarly demonstrated elevated levels of MVs in CRC patients, supporting our data and further pointing out the role of MVs as a potential biomarker for early disease detection [21].…”
Section: Discussionsupporting
confidence: 82%
“…The prevention and treatment of colorectal cancer (CRC) is a global health challenge since CRC ranks as the second leading cause of cancer-related mortality [20]. Recent studies highlight the importance of microvesicles as biomarkers for the early detection of CRC [21], prognosis, and the prediction of response to therapy [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…EXOs (~40-150 nm) are intraluminal vesicles (ILVs) contained in MVBs, which are released into the extracellular environment upon fusion with the plasma membrane [5,60,61]. Unlike MVs and despite sharing common intracellular mechanisms and sorting machinery, EXOs are formed through a distinct and complex intracellular regulatory process that determines their composition and functions [8,61].…”
Section: Egfr and Ev Biogenesismentioning
confidence: 99%